Pengembangan Modul Bimbingan Karir Teori Anne Roe Terhadap Perencanaan Karir Siswa: Pengembangan Modul Bimbingan Karir Teori Anne Roe Terhadap Perencanaan Karir Siswa - Turrohmah, Habiba; Karamoy, Yurike Kinanthy; Prawita, Sri (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
A module is a set of subject matter that is arranged systematically and sequentially to make it easier for students to achieve appropriate competencies accompanied by guidelines for use. The existence of modules can be utilized by BK teachers to carry out services in schools such as career guidance for student career planning. This research aims to create a module design regarding Anne Roe's career planning theory in order to produce a module that is suitable for use by class VIII students at SMPN 03 Tanggul. This research uses R&D (Research and Development) development research using the Borg and Gall development model which includes 6 of 10 stages, namely: Research and information collecting, Planning, Develop preliminaryform of product, Preliminary field testing, Main product revision, Research subjects include: Expert Test 1 tests the suitability of the material for the product, Expert Test 2 tests the suitability of the product for BK services. The data collection method uses a questionnaire. There is a questionnaire used or called a validation sheet which is used by expert tests. The results of this research assessment include: expert test 1 obtained a percentage score of 73% with good criteria and stated that the module, while expert test 2 obtained a percentage score of 91% with very good criteria. The results of small group test calculations consisting of 6 class VIII students at SMPN 03 Tanggul showed that the practicality percentage value of the module developed was 72%, which was declared